Nonnegative mixed states in Weyl-Wigner-Moyal theory - Gracia Bondía, José M. (1988)
We classify the gaussian Wigner functions corresponding to mixed states and show that, unlike the case of pure states, not all nonnegative mixed states are gaussian.